Does vitamin D replacement therapy cause a regression in fatty liver disease? A case control study of comparison of vitamin D and other common therapy modalities - Abdurahmanov, Vusal; Güntürk, Arzu; Kartufan, Fatma; Nurmuhammedov, Rahman; Küçükardalı, Yaşar (Journal of Surgery and Medicine, 2021)
Background/Aim: Non-alcoholic fatty liver is quite common among modern populations, and simpler methods are researched for its early diagnosis and therapy. Studies are stating that vitamin D deficiency could play a role in the etiopathogenesis of fatty liver. This study aimed to compare the efficacy of metformin and vitamin D therapy in improving fatty liver disease. Methods: A total of 86 patients with non-alcoholic fatty liver disease were included in this case control study and classified into four groups according to the treatment received. In the study group, 23 patients were using metformin only, and 21 patients were using both metformin and vitamin D. Twenty-one patients were using vitamin D only, and 21 patients were on a diet and an exercise regimen (control group). Weight, BMI, waist circumference, fatty liver index (FLI), HOMA-IR, AST, ALT, GGT, triglyceride parameters were evaluated before and after four weeks of therapy. Results: There was a significant regression in the fatty liver disease of the patients who used both metformin and vitamin D (FLI-%5, 90 (11.1) P=0.025). Among patients who used only metformin and only vitamin D, the decrease in FLI was not significant (P>0.05); however, FLI was observed to significantly decrease in the control group (-7.30, P=0.018). The serum CRP levels were also observed to significantly decrease in the control, Met and Met-D vit groups (P=0.025, P=0.002, P=0.006, respectively). Conclusions: The combination of vitamin D and metformin therapy could positively contribute to the improvement of NAFLD in patients with vitamin D deficiency.